ColE1 plasmid mutants affecting growth of an Escherichia coli recB recC sbcB mutant. - Inselburg, J (1978)
Three mutant derivatives of the plasmid ColE1 were found to reduce the formation of plasmidless cells in a recB recC sbcB cell population. An active plasmid role in the plasmid-host interaction is suggested.